ANALISA PENANGANAN KOMPLAIN PELANGGAN DI GO-KART LEMBANG SPEEDWAY - Ageng saepudin kanda S; Salma hasna hamidah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Research Method This research uses qualitative methods so that researchers are able to think and build their own knowledge. This research raises a deep phenomenon, until it finds logical answers from the research results and questions in the research. Based on the results of interviews conducted with the Go-Kart Lembang Speedway Owner and Lembang Speedway Go-Kart Supervisor as follows: Customer Complaints, Types of Customer Complaints, Causes of Customer Complaints, Customer Complaint Handling System, Benefits of Handling Complaints. So the researcher can draw the conclusion: Complaint handling at Go-Kart Lembang Speedway has been effective. Complaints submitted by customers at Go-Kart Lembang Speedway are regarding height and weight, queue line problems, customers who do not comply with regulations, expensive prices, In handling complaints at Go-Kart Lembang Speedway which acts as a media for customer complaints. Steps taken: receiving complaints, following up on complaints.